Taxation, innovation and the environment - Ash, Michael (OECD, 2010)
"OECD governments are increasingly using environmentally related taxes because they are typically one of the most effective policy tools available. Exploring the relationship between environmentally related taxation and innovation is critical to understanding the full impacts of this policy instrument as well as one potential facet of 'green growth'. By putting a price on pollution, do environmentally related taxes spur innovation? What types of innovation result? Does the design of the tax play a critical role? What is the effect of this innovation? In analyzing these questions, this report draws on case studies that cover Japan, Korea, Spain, Sweden, Switzerland, the United Kingdom, Israel and others. It covers a wide set of environmental issues and technologies, as well as the economic and policy contexts. The research methods range from econometric analysis to interviews with business owners and executives. The report also explores the use of environmentally related taxes in OECD countries and outlines considerations for policymakers when implementing these taxes."--Publisher's description.